Ahsanu Taqwim's Human Concept in the View of Said Nursi and Its Influence on Personality - Azhar Afif Abu Abdurrasyid (Tasfiyah: Jurnal Pemikiran Islam, 2021)
Man has the best personality and ubūdiah because it is the perfect creation of God,  However, it is the human self that makes his personality bad. This article attempts to explain the concept of man aḥsan al-Taqwīm (created in the best form) in the view of Said Nursi and it influence on a personality. This discussion uses analytical methods as a development of descriptive methods, The discussion step begins with the disclosure of the concept of man aḥsan al-Taqwīm in the Treatise of Nur by Badiuzzaman Said Nursi and at the end of the discussion described the influence of the concept in a personality. The results of this discussion can be concluded in several points. First, man is God's extraordinary creation, showing all the manifestations of asmaul husna that make man the orbit of all his carvings and as miniatures and models of all natural entities. Second, in man there are two sides: egoism and ubudiah, The process of ahsanu taqwim in man exists because it leaves the ego ismī (shows itself) and turns the potential of evil into the potential of good. Third: personality is divided into three, mutma'innah, lawwamah and ammarah. Fourth, in fact, the human personality has a perfect nature in accordance with the concept of ahsanu taqwim which has an element of faith in it.  But denial and unbelief hinder the meaning of asmaul husna carvings. And make a person's personality imperfect even bad.